Nonfinancial Defined Contribution Pension Schemes in a Changing Pension World : Volume 2. Gender, Politics, and Financial Stability - Holzmann, Robert (Washington, DC: World Bank, 2013)
The concept of nonfinancial (notional) defined contribution (NDC) was born in the early 1990s and implemented from the mid-1990s in a number of countries. This innovative unfunded individual account scheme emerged and created high hopes at a time when the world seemed to have been locked into a stalemate between making piecemeal reforms of ailing traditional pay- as-you-go defined benefit schemes and introducing prefunded financial account schemes. Nonfinancial (notional) defined contribution (NDC) plans are designed to eliminate the work disincentives and nontransparent redistributions of defined benefit (DB) social security schemes without the transition costs and risk shifting that occurs in the context of a switch to a funded defined contribution (DC) scheme. To a large extent, they sweep away the special privileges that, intentionally or inadvertently, accrue to various groups in traditional schemes and pay everyone in accordance with his or her own contributions. However, not surprisingly, these new provisions will have different effects on diverse population subgroups, including men and women. Most of the effects do not stem from explicit gender-specific provisions in the plans, but rather from the interaction of gender-free policies with differing demographic and employment characteristics of men and women. The same policies affect the two genders differently because of the more limited labor force attachment of women as a result of their childbearing and childrearing roles, their lower earnings when they do work, their longer life expectancy, and the likelihood that they will eventually become widows and live alone in very old age. Both financial defined contribution (FDC) and NDC plans make certain design choices explicit that are implicit in DB plans. Although this feature allows for more informed decision making, it can also be politically sensitive and divisive. In some cases, the decision process is simpler for NDC plans than for FDC plans. NDC plans do not have individual investments and, therefore, do not have the problems that FDCs face and that stem from decentralized investment decisions.